User centred design in smart homes: research to support the equipment and services aggregation trials - Victoria Haines; Martin Maguire; Catherine Cooper; Val Mitchell; Fran Lenton; Hina Keval; Colette Nicolle (2005)
This document reports on the studies carried out by ESRI within the TAHI Equipment Management (EM) and Services Aggregated (SA) trials. Background research into interface design and user needs was conducted at a generic level in order to guide the development of specific user interfaces for the Services Aggregation trial (through a television) and the Equipment Management trial (through a PC device).